Tracing Progress in Children's Executive Functioning and Language Abilities Related to Reading Comprehension via ExeFun-READ Intervention - Iveta Kovalčíková; Jochanan Veerbeek; Bart Vogelaar; Martin Klimovič; Eva Gogová (MDPI AG, 2024)
One important internal factor influencing reading comprehension is a child's executive functioning. The primary objective of this paper is to evaluate the effectiveness of a cognitive stimulation program, ExeFun-READ (a program focusing on executive functioning stimulation via the L1 (Slovak language) curriculum with a specific focus on enhancing reading comprehension). The program is explicitly based on the assumed bi-directional relationship between executive functioning and language abilities related to reading comprehension. The program is domain-specific; the curriculum of L1 (Slovak) is a curricular area in which cognitive mediation occurs. The study will investigate whether the domain-specific ExeFun-READ intervention had a positive effect on children's executive functioning and language subcomponents of reading comprehension. Keeping in mind ecological validity, ExeFun-READ was designed primarily for educational purposes, specifically professional tutoring for low-performing students. The intervention consists of 30 units; each unit lasts for 45-60 min. A stimulation unit approximates a teaching unit rather than a clinical experimental intervention. In total, 151 low-performing students attending grade four from seven elementary schools took part in the project. The study employs a pre-test-training-post-test design with three conditions: experimental, active control, and passive control. In the current study, the intervention led to improved language abilities related to reading comprehension. Significant improvements were found in vocabulary (semantic knowledge), completion of sentences (syntactic knowledge), and classification of terms (verbal fluency and inferencing) in the group of children that received the ExeFun-READ intervention. In terms of executive functioning, the improvement only extended to switching fluency.